Evaluation of the Allelopathic Activity of Albizia procera (Roxb.) Benth. as a Potential Source of Bioherbicide to Control Weeds - Kawsar Hossen; Hisashi Kato-Noguchi (International Journal of Plant Biology, 2022)
Agricultural production depends heavily on the application of synthetic herbicides. Using these herbicides results in the development of herbicide-resistant weeds, poses hazards to human and animal health, and pollutes the environment. To solve these problems, developing and using bioherbicides must be increased. Although different uses of Albizia procera have been well reported, its allelopathic activity against weeds and crop species has not. Hence, we evaluated the allelopathic activity of the A. procera plant and isolated its allelopathic compounds. Extracts of A. procera significantly suppressed the seedling growth of the tested species (cabbage, alfalfa, lettuce, barnyard grass, timothy, and Italian ryegrass). The seedling growth decreased with increasing extract concentrations. The concentrations required for 50% growth inhibition (I50 value) of the tested plants were 0.0225–0.4935 mg/mL. The A. procera extracts were separated using different column chromatography, and two active fractions (AP-5 and AP-7) were isolated. Cress seedling growth was completely restricted by fraction AP-5, and fraction AP-7 restricted the cress shoots to 83.10% and roots to 85.65% of the control treatment. The findings of this study indicate that A. procera extracts have allelopathic activity and these fractions might contribute to the activity.